Drug-related Problems Among Type 2 Diabetic Patients With Hypertension in a Tertiary Care Hospital in Lebanon: A Cross-sectional Study - Georges Hatem; Aya Awarkeh; Lynne H Jaffal; Dalia Khachman; Amal Al-Hajje; Salam Zein (Pharmaceutical and Biomedical Research, 2023)
Background: Patients with type 2 diabetes (T2D) often have other associated comorbidities, making them susceptible to drug-related problems (DRPs) which can adversely affect their quality of life. Understanding these problems can provide baseline data to allow informed health decisions and effective management of patients. Objectives: This study aims to investigate DRPs in T2D patients with hypertension and find the predictors of these problems. Methods: This cross-sectional study was conducted for six months in the internal medicine department of a tertiary care hospital in Lebanon. Participants were 135 adult T2D patients with hypertension who were receiving one or more anti-diabetes drugs, and at least one medication for hypertension. Pharmaceutical care network europe classification system was used to classify the DRPs. Data were collected by two clinical pharmacists using a self-report tool. Results: Most of patients were female. Most of them (94.1%) had at least one DRP (1.43±0.72 per patient). “Non-optimal drug treatment effect” was the most frequent problem (48.2%). Achieving the HbA1C target reduced the odds of this problem by 66.6%, while the increased serum creatinine level caused a two-fold increase in this problem. The use of angiotensin-converting enzyme inhibitors or angiotensin receptor blockers reduced the odds of DRPs by 86.2% and 83.3%, respectively, while lipid-lowering and anti-anginal drug use caused a four-fold increase in DRPs. Conclusion: Early identification of DRPs in diabetic patients with hypertension and their associated factors can help improve their management and reduce the associated mortality and morbidity rates.